Human papillomavirus infection: update on virological and epidemiological aspects and diagnosis - Cavalcanti, Silvia MB; Carestiato, Fernanda N (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Human papillomavirus are small DNA viruses capable of infecting the epithelium of skin and mucosa. More than a hundred types have already beendescribed, and nearly 40 promote sexually transmitted diseases. It is in the genital tract that 13 HPV types exert their oncogenic potential, being res-ponsible by the death of 200,000 women worldwide, annualy. The available diagnosis to STD and cancer control is based upon the colposcopy, cyto-logy and histopathology tools, and can be laboriatorially confirmed by molecular biology techniques: PCR and hybrid capture. Recently, two prophy-lactic vaccines against HPV types 6, 11, 16 e 18 (Merck) and 16 e 18 (Glaxo) were developed. They are composed by VLP (Virus-like particles)expressed in yeasts. Promissing results have been published. Nevertheless, immunological mechanisms for human defense are not well elucidated.